DEFINING EVANGELICALISM: QUESTIONS THAT COMPLEMENT THE QUADRILATERAL. - Worthen, Molly (Fides et historia, 2015)
The article comments on a definition of evangelicalism as discussed in the book "Evangelicalism in Modern Britain: A History From the 1730s to the 1980s" by David W. Bebbington. It discusses several elemental concerns that unite Protestants whom the author considers as evangelical including the separation between spiritual and rational knowledge. It also suggests that evangelicals are not separated from mainstream culture and that they have always been caught up in it.